The neurophysiological response to manual therapy and its analgesic implications: A narrative review - Vigotsky,Andrew D; Bruhns,Ryan P (PeerJ PrePrints, 2015)
Manual therapy has long been a component of physical rehabilitation programs, especially to treat those in pain. The mechanisms of manual therapy, however, are not fully understood, and it has been suggested that its pain modulatory effects are of neurophysiological origin, and may be mediated by the descending modulatory circuit. Therefore, the purpose of this review is to examine the neurophysiological response of different types of manual therapy, in order to better understand the neurophysiological mechanisms behind each therapy’s analgesic effects. It is concluded that different forms of manual therapy elicit analgesic effects via different mechanisms. Additionally, future avenues of mechanistic research pertaining to manual therapy are discussed.
Keywords: pain; analgesia; manual therapy; descending modulation; spinal manipulation; massage; acupressure; endopharmacology; chiropractic; osteopathy